2019
DOI: 10.3390/catal9030219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preparation Method of Co-Ce Catalysts on CH4 Combustion

Abstract: Transition metal oxides have recently attracted considerable attention as candidate catalysts for the complete oxidation of methane, the main component of the natural gas, used in various industrial processes or as a fuel in turbines and vehicles. A series of novel Co-Ce mixed oxide catalysts were synthesized as an effort to enhance synergistic effects that could improve their redox behavior, oxygen storage ability and, thus, their activity in methane oxidation. The effect of synthesis method (hydrothermal or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This behavior was again seen during the following dry-humid operation cycles, and suggested that water inhibition was essentially caused by the coverage of the surface that limited the extent of the reaction methane and catalyst oxygen active species. This effect has been also observed in other works, and has been generally been linked to the weak adsorption potential that water molecules have on the surface of cobalt oxide [67,68]. In particular, Geng et al [69] observed a significant increase in the intensity of the DRIFTS absorption bands from hydroxyl groups in a Co/γ-Al 2 O 3 catalyst when water vapor was added to the feed.…”
Section: Resultssupporting
confidence: 66%
“…This behavior was again seen during the following dry-humid operation cycles, and suggested that water inhibition was essentially caused by the coverage of the surface that limited the extent of the reaction methane and catalyst oxygen active species. This effect has been also observed in other works, and has been generally been linked to the weak adsorption potential that water molecules have on the surface of cobalt oxide [67,68]. In particular, Geng et al [69] observed a significant increase in the intensity of the DRIFTS absorption bands from hydroxyl groups in a Co/γ-Al 2 O 3 catalyst when water vapor was added to the feed.…”
Section: Resultssupporting
confidence: 66%
“…Exploring the effect of the synthesis method of other Co-doped ceria systems on the catalytic performance in complete methane oxidation led to the preparation of two series of catalysts with Co content ranging from 2 to 15 wt% via an incipient wetness impregnation method on ceria supports manufactured by hydrothermal and precipitation technique [174]. The mixed oxides with supports produced by the hydrothermal method showed superior textural characteristics with BET surface area between 80-100 m 2 /g and CeO 2 particle size of around 6-9 nm, compared to those obtained through the precipitation method which have surface areas of 39-43 m 2 /g and ceria particle size of 16-20 nm.…”
Section: Monometallic Modified Ceria Catalystsmentioning
confidence: 99%
“…On the other hand, a major part of contributions (9/21) concerns original research on nitrogen oxides reduction processes [20][21][22][23][24][25][26][27][28], reflecting the fact that this topic still remains hot among the targets of environmental catalysis. Five out of 21 studies concern CO and hydrocarbons oxidation processes [29][30][31][32][33] while the remained 4/21 concern CO 2 capture/recycling processes under the view of cyclic economy [34][35][36][37].…”
Section: Special Issue Contributions and Highlightsmentioning
confidence: 99%
“…As a consequence, control of CH 4 emissions via catalytic deep oxidation has attracted considerable renewed attention, given that methane appears the lowest reactivity among alkanes. Under this view, Iliopoulou and co-workers [31] synthesized a series of novel Co-Ce mixed oxide catalysts in an effort to enhance synergistic effects that could improve their redox and oxygen storage properties and, thus, their activity in methane deep oxidation. The effect of the synthesis method (hydrothermal or precipitation) and Co loading (0, 2, 5, and 15 wt%) on the catalytic efficiency and stability was investigated.…”
Section: Co Ch 4 and Other Hydrocarbons Oxidation Reactionsmentioning
confidence: 99%